Food Safety: Play It Safe With Eggs - Linda B. Bobroff; Jennifer Hillan (EDIS)
Fresh eggs may contain bacteria that can cause salmonellosis. This foodborne illness causes vomiting and diarrhea. It can be severe and even fatal in older adults. Reduce your risk for this foodborne illness by following these guidelines. This 1-page fact sheet was written by Linda B. Bobroff and Jennifer Hillan and published by the UF Department of Family Youth and Community Sciences, June 2013.